Solvent Effects on the Reversible Intercalation of Magnesium‐Ions into V2O5 Electrodes. Issue 22 (5th September 2018) - Attias, Ran; Salama, Michael; Hirsch, Baruch; Gofer, Yosef; Aurbach, Doron
Abstract: The choice for solvents in electrolyte solutions for non‐aqueous magnesium batteries is currently limited to ethers. However, the scientific community regularly uses acetonitrile (ACN) based electrolyte solutions as model systems in order to characterize new cathode materials for rechargeable Magnesium batteries. In this study, we demonstrated the effect of dimethoxyethane (DME), an important solvent for rechargeable magnesium systems, on the reversible intercalation of Mg 2+ cations into thin, monolithic V2 O5 films. The effect of DME on the intercalation kinetic have been examined via chronopotentiometry, galvanostatic and galvanostatic intermittent titration (GITT) measurements. In addition, we explored basic scientific questions related to the structure of ACN:DME based electrolyte solutions via Raman spectroscopy and surface chemistry of V2 O5 /Mg(ClO4 )2 /ACN:DME systems via X‐ray photoelectron spectroscopy. We found that addition of DME to the Mg(ClO4 )2 /ACN solution results in replacing the ACN‐Mg 2+ cation by the more thermodynamically stable 3DME‐Mg 2+ solvate structure. We also found that the DME‐Mg interaction forms stable solution structures that kinetically slow down the insertion of the Mg 2+ cations into V2 O5, compared with the less coordinated situation in solutions based solely on ACN. Abstract : Intercalation kinetics : the effect of dimethoxyethane (DME) on the intercalation of Mg 2+ cations into thin V2 O5 films as cathode for Mg batteries is investigated. The structure of acetonitrile (ACN):DME based electrolytes is investigated via Raman spectroscopy. Addition of DME to Mg(ClO4 )2 /ACN solutions results in the formation of thermodynamically more stable 3DME‐Mg 2+ solvate structure, slowing down the insertion of the Mg 2+ cations into V2 O5 .